A Non-Exact Approach and Experimental Studies on the Combinatorial Auction Problem - GUO, Yunsong (Institutional Knowledge at Singapore Management University, 2005)
In this paper we formulate a combinatorial auction brokering problem as a set packing problem and apply a simulated annealing heuristic with hybrid local moves to solve the problem. We study the existing exact and non-exact approaches to the problem and analyze the performance of those approaches. We compared our heuristic with the leading exact method CPLEX 8.0 solver and another non-exact algorithms Casanova using both the CATS test sets and test cases believed more difficult than CATS. Results show that the method is competitive with CPLEX 8.0 and obtains near optimal solutions for the CATS cases and up to 15% and 40% better solutions compared with CPLEX and Casanova, respectively, when the other instances were used.